2015
DOI: 10.1186/s13104-015-0979-1
|View full text |Cite
|
Sign up to set email alerts
|

Physical education or playtime: which is more effective at promoting physical activity in primary school children?

Abstract: BackgroundSchool physical education (PE) and playtime provide important opportunities for physical activity (PA). However, little research has assessed PA during primary school PE using accelerometry or compared PA during different lesson types. There is also a lack of research comparing PA during PE and playtime, despite suggestions that playtime promotes more PA. The primary aim of this study was to determine which types of PE lesson are most facilitative of PA. The secondary aim was to determine whether chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 24 publications
3
22
1
1
Order By: Relevance
“…Moreover, very few studies have compared MVPA between the types of exercises performed during PE with using accelerometry in primary school children [ 2 ]. Wood and Hall [ 4 ] found that children aged 8–9 years engaged in significantly higher MVPA during team games (e.g., football) compared to movement activities in PE lessons (e.g., dance). However, they did not report on the levels of sedentary time during PE lessons.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, very few studies have compared MVPA between the types of exercises performed during PE with using accelerometry in primary school children [ 2 ]. Wood and Hall [ 4 ] found that children aged 8–9 years engaged in significantly higher MVPA during team games (e.g., football) compared to movement activities in PE lessons (e.g., dance). However, they did not report on the levels of sedentary time during PE lessons.…”
Section: Introductionmentioning
confidence: 99%
“…It causes joy in children, promotes movement in learning forward. It helps to solve the main problem of physical activity of schoolchildren of any age and sexual di erences (Wood & Hall, 2015). e implementation of the competitive method is noted in physical education lessons when performing the exercise «Classic's», when schoolchildren try to perform the exercise at high speed, competing with each other.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, one of the spaces that make up the adolescents' environment for a large part of their lives is the school, which is also an important place for health promotion and active lifestyle [7][8][9] . This can be achieved through well-organized physical education classes with active recesses and structures that favor the development of such interventions [10][11][12] . In this sense, studies have shown that more structured schools, places for outdoor physical activity, plain and adequate spaces and greater number of multi-sport courts have a positive impact on the sufficiently active behavior of adolescents [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, physical education teachers play a relevant role, because it is possible to perceive that even in schools with low-quality structure, when the class is well planned and structured 10,11 , there are good levels of PA 7 , which does not necessarily depend on environmental and structural aspects.…”
mentioning
confidence: 99%